Principles and techniques of trauma-centered psychotherapy. - Johnson, David Read; Lubin, Hadar (Amer Psychiatric, 2015)
This is not a general text, then, but one focused on building competence and confidence in trauma-centered interventions, providing methods that should be readily and widely applicable to clinical practice.